2023
DOI: 10.21203/rs.3.rs-3432774/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis of Zika virus NS1 multimerization and human antibody recognition

Dahai Luo,
Bing Liang Alvin Chew,
An Qi Ngoh
et al.

Abstract: The Zika virus (ZIKV) is a mosquito-transmitted flavivirus related to the dengue virus that has emerged in recent global outbreaks, with previously unreported neurological or birth abnormalities. There remains a large, unmet need for efficacious vaccines and antiviral agents against ZIKV. Flavivirus non-structural protein 1 (NS1) is the only secreted viral protein that has proven useful in diagnostics. However, its physiologically relevant structural forms and pathogenesis mechanisms remain unclear. While many… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This discrepancy could be attributed to differences among these flavivirus species or variations in the expression and purification conditions. Another study by Luo et al (28) observed filaments of NS1 tetramers in the cryo-EM micrographs. We did not observe similar long filaments in our collected micrographs.…”
Section: Discussionmentioning
confidence: 93%
“…This discrepancy could be attributed to differences among these flavivirus species or variations in the expression and purification conditions. Another study by Luo et al (28) observed filaments of NS1 tetramers in the cryo-EM micrographs. We did not observe similar long filaments in our collected micrographs.…”
Section: Discussionmentioning
confidence: 93%